Union Budget 2020: What is in Store for Agriculture? - Verma, Ravindra (Indian Farming, 2020)
A sort of panic usually grips the people before the budget is presented in the house. However, this time, expectation rather than trepidation was the hallmark of the pre-budget days. The agricultural sector was ready with its long wish list expecting big announcements in the Union Budget 2020-21. There were talks about increased fund allocation to schemes aimed at improving farmers’ incomes, besides those meant to address the issues of irrigation networks. Well the optimists surely have something to rejoice. The government’s 16-point action plan is definitely a steroid shot to revive the agricultural sector and to double the income of the farmers by 2022. It also bespoke of the government endeavour to utilize the last year of the decade for making rapid progress so that we may enter the next decade on a better note.